Administration of Metabiotics Extracted From Probiotic Lactobacillus rhamnosus MD 14 Inhibit Experimental Colorectal Carcinogenesis by Targeting Wnt/β-Catenin Pathway - Sharma, Mridul; Shukla, Geeta (Frontiers in Oncology, 2020)
Background and objective: The cellular microenvironment, diet and lifestyle play key role in the occurrence of colorectal cancer. Due to its rising trend, attempts are being made to devise novel bio-interventions as adjunct to conventional therapies to prevent this deadly disease. “Metabiotics”, the beneficial metabolic signatures of probiotics are emerging as potential anticancer agent due to their ability to alter metabolic processes in the gut lumen and reduce the severity of colon carcinogenesis. Though beneficial attributes of metabiotics have been elucidated in vitro, yet their anticancer mechanism in vivo needs to be explored. Thus, the present study was performed to envisage anticancer potential of metabiotic extract obtained from indigenous probiotic, Lactobacillus rhamnosus MD 14 in early experimental colon carcinogenesis. Materials and Methods: Sprague-Dawley rats were daily administered with low, medium and high dose of metabiotic extract orally along with a single dose of weekly intra peritoneal injection of 1, 2-dimethylhydrazine up to six weeks and monitored for the markers of early colon carcinogenesis. Results: It was observed that the medium dose of metabiotic extract attenuated early colon carcinogenesis by reducing fecal procarcinogenic enzymes, oxidants, aberrant crypt foci, vis- a -vis downregulating oncogenes (K-ras, β-catenin, Cox-2, NF-κB) and upregulating tumor suppressor p53 gene leading to almost normal colon histology. Conclusions: It can be suggested that metabiotics modulate experimental colorectal cancer and could be used as a promising alternative of probiotics, particularly in immunocompromised individuals.